2016
DOI: 10.1177/0042098015612984
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the urban smart grid: Socio-technical experimentation in the city of Austin

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 42 publications
0
49
0
5
Order By: Relevance
“…One such strategy is the smart city, which stresses the digitalization of the city (Anttiroiko ). Examples include Amsterdam Smart City (Raven et al ) and the Pecan Street Smart Grid project in Austin, Texas (McLean et al ). Cities have also led the way in creating experimentation platforms such as living labs (Tukiainen et al ; Gascó ; Kronsell and Mukhtar‐Landgren ; Raven et al ).…”
Section: A Typology Of Governance Platformsmentioning
confidence: 99%
“…One such strategy is the smart city, which stresses the digitalization of the city (Anttiroiko ). Examples include Amsterdam Smart City (Raven et al ) and the Pecan Street Smart Grid project in Austin, Texas (McLean et al ). Cities have also led the way in creating experimentation platforms such as living labs (Tukiainen et al ; Gascó ; Kronsell and Mukhtar‐Landgren ; Raven et al ).…”
Section: A Typology Of Governance Platformsmentioning
confidence: 99%
“…A large body of work has arisen in recent years -particularly within Science and Technology Studies, although not exclusivelyexamining the interplay between the organisation of society and the development of smart or future energy technology landscapes (Walker, Karvonen, & Guy, 2015;Bickerstaff, Hinton, & Bulkeley, 2016;McLean, Bulkeley, & Crang, 2016;Groves et al, 2016;Strengers & Nicholls, 2017) of which energy feedback is often regarded as "the first step" (Ballo, 2015, p.9). This work has tended to be grounded by the 'sociotechnical' paradigm, within which there is a clear acknowledgement of the co-evolving relationship between social expectations or visions and technical possibilities (Guy, 2006 (Hargreaves, Nye, & Burgess, 2010, p.6113), emphasising the variety of forms these reasons could take, and thus the multiple nature of evaluations of success.…”
Section: Multiple and Dynamic Experiences Of Smart Energy Technologiesmentioning
confidence: 99%
“…Numerous ecological modernisation policies have "already deftly demonstrated that such 'win-win' approaches to urban problems subsume environmental issues under neoliberalised concerns of 'efficiency, competitiveness, marketability, flexibility and development'" (Laidley, 2007: 261). It may be that developments towards smart cities could further splinter existing infrastructures (McLean, Bulkeley and Crang, 2016).…”
Section: Technological Integrationmentioning
confidence: 99%